The Catch-A-Wave Theory of Adaptability: Core Competencies for Developing Gifted Behaviors in the Second Machine Age of Technology - Renzulli, Joseph S. (International Journal for Talent Development and Creativity)

(untitled) (International Centre for Innovation in Education/Lost Prizes International, 2020)
In this article, I describe a series of Five Core Competencies that gifted education specialists should consider integrating into their teaching to respond to the many changes that are taking place in technology, work, and career preparation. Although the focus of this theory is on high- level jobs usually pursued by college graduates and advanced degree students, this work also has relevance for the general-education community because future employment at all levels will require various degrees of proficiency in the Core Competencies discussed below. Students who will pursue college degrees and professional level jobs will need to attain advanced levels of these skills, have the opportunity to explore a wide range of skills, and be able to learn them more rapidly. Students should be placed in learning situations that require the adaptability that is the theme of this article so that they will learn to apply the skills in ways that will lead to success in job-transformational situations. Leadership and advanced-level positions require high levels of both performance and flexibility in the competencies that will be discussed below. The Catch-A-Wave Theory of Adaptability will be introduced with the presentation of background information and a rationale for the theory. The theory itself along with the five Core Competencies included in the theory will follow and then be supplemented with a section that provides strategies and resources for developing those competencies.